2021
DOI: 10.15252/embj.2020107192
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor FOXP2 is a flow‐induced regulator of collecting lymphatic vessels

Abstract: The lymphatic system is composed of a hierarchical network of fluid absorbing lymphatic capillaries and transporting collecting vessels. Despite distinct functions and morphologies, molecular mechanisms that regulate the identity of the different vessel types are poorly understood. Through transcriptional analysis of murine dermal lymphatic endothelial cells (LECs), we identified Foxp2 , a member of the FOXP family of transcription factors implicated in speech development, as a collectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…In contrast, all these genes have been reported to be consistently upregulated in murine dermal collecting LECs. 13 Correspondingly, distinct gene enrichment analyses revealed that although Icam1 hi LECs were mainly associated with leukocyte migration, Foxp2 hi LECs were mainly related to the regulation of apoptosis or oxidative stress pathways (Figure 3D). Meanwhile, a Spearman correlation analysis with LEC subsets isolated from normal aortas ( Lyve1 hi / Ccl21a hi initial LECs and Lyve1 low / Ccl21a low collecting LECs; Figure S2E and S2F) showed lesser comparability within the collecting LECs of grafted aortas, reflecting their greater heterogeneity after transplantation (Figure 3E).…”
Section: Resultsmentioning
confidence: 90%
“…In contrast, all these genes have been reported to be consistently upregulated in murine dermal collecting LECs. 13 Correspondingly, distinct gene enrichment analyses revealed that although Icam1 hi LECs were mainly associated with leukocyte migration, Foxp2 hi LECs were mainly related to the regulation of apoptosis or oxidative stress pathways (Figure 3D). Meanwhile, a Spearman correlation analysis with LEC subsets isolated from normal aortas ( Lyve1 hi / Ccl21a hi initial LECs and Lyve1 low / Ccl21a low collecting LECs; Figure S2E and S2F) showed lesser comparability within the collecting LECs of grafted aortas, reflecting their greater heterogeneity after transplantation (Figure 3E).…”
Section: Resultsmentioning
confidence: 90%
“…5 C ). Based on the expression of known LEC subtype markers, the clusters were annotated as valve LECs ( Cldn11 + ; Takeda et al, 2019 ), collecting vessel LECs ( Foxp2 + ; Hernández Vásquez et al, 2021 ), and capillary LECs ( Lyve1 high ; Fig. 5 C ).…”
Section: Resultsmentioning
confidence: 99%
“…Each cluster included an equal contribution of cells from the 3 control samples ( Figure 5D ). Based on the expression of known LEC subtype markers, the clusters were annotated as valve LECs ( Cldn11 + ) (30), collecting vessel LECs ( Foxp2 + ) (31), and capillary LECs ( Lyve1 high ) ( Figure 5, B-D ). Trajectory analysis based on gene expression data suggested phenotypic progression from collecting vessel to capillary LECs ( Figure 5, C-E ), which mirrors anatomical positioning of so called pre-collecting vessels that share molecular and functional features of the two vessel types (32).…”
Section: Resultsmentioning
confidence: 99%